2021
DOI: 10.18186/thermal.977996
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation on performance evaluation among metal and oxide based nanofluids for power savings application of a circular tube

Abstract: The advancement of heat transfer techniques is a challenge to the researcher in this era. Implementation of nanotechnology is one of the potential techniques which enhance the heat transfer rate in a significant amount. Subsequently, nanotechnology can reduce the requirement of pumping power. However, suspension of nanoparticle with liquid to produce a new working fluid called nanofluid which has better thermal and fluid dynamic properties in comparison to pure liquid is introduced as a typical nanotechnology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Agarwal et al [3] observed that nanofluids were shown to be very stable in lower volume fractions compared with the higher volume fraction. The utilization of nanofluids will remarkably raise the heat transfer coefficient, while at the same time, dramatically increase thermal conductivity, viscosity, particle size and particle concentration [4][5][6][7][8][9][10]. Moreover, energy is an important topic, and effective utilization of energy can reduce environmental emissions [11].…”
Section: Introductionmentioning
confidence: 99%
“…Agarwal et al [3] observed that nanofluids were shown to be very stable in lower volume fractions compared with the higher volume fraction. The utilization of nanofluids will remarkably raise the heat transfer coefficient, while at the same time, dramatically increase thermal conductivity, viscosity, particle size and particle concentration [4][5][6][7][8][9][10]. Moreover, energy is an important topic, and effective utilization of energy can reduce environmental emissions [11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Rabby et al (2021), Kusworo et al (2020), Kumar et al (2017), and several researchers conducted studies related to nanofluids due to the advancement of nanofluids.…”
Section: Introductionmentioning
confidence: 99%